The effect of banana Xanthomonas wilt on beer-banana value chains in Central Uganda: an exploratory study - Rietveld, Anne M.; Jogo, W.; Mpiira, S.; Staver, Charles (Emerald Publishing Limited, 2014)
– Beer-bananas in Central Uganda are important for smallholder farmers’ livelihoods, especially for those that process the banana into beer and spirits. The purpose of this paper is to understand how actors in the beer-banana value chain are affected and how they are managing disease has become an important issue since the outbreak of the bacterial banana disease Xanthomonas Wilt.– The authors conducted an exploratory study focusing on producers of beer-bananas; brewers and non-brewers, and on retailers in Central Uganda and in Kampala. The authors conducted surveys with these value chain actors and we used baseline data, collected through a household survey in the project sites.– Results showed that Banana Xanthomonas Wilt (BXW) has drastically reduced productivity of beer-banana systems, resulting in reduced sales volumes of beer-bananas and processed products and consequently reduced incomes. Application of disease control measures was generally higher among those farmers that brew.– This being an exploratory study, the samples for the different value chain actors were rather small. Future research should address: product quality and opportunities for differentiation; effects of beer-banana processing on rural communities; adoption of BXW control measures.– Beer-bananas are often neglected in research; this paper shows that is unfounded since beer-banana production and processing are important for many people’s livelihood. More insight into what motivates farmers to control the disease is essential to protect these people’s livelihoods.